Penerapan Problem based learning (PBL) Untuk Meningkatkan Kemampuan Kognitif Siswa Pada Materi Perkalian Kelas Iii Sekolah Dasar - Septian Rizky Purwanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to improve the cognitive abilities of third-grade elementary school students in multiplication material through the implementation of the Problem Based Learning (PBL) model. The research was conducted at SDN Padaan 02, Pabelan, Semarang Regency, involving 8 students as the research subjects. The research method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was carried out in two cycles consisting of planning, implementation, observation, and reflection stages. Data collection techniques included cognitive tests, observation of student activities, and documentation. The results showed that the implementation of Problem Based Learning (PBL) was able to improve students’ learning activities and learning outcomes. In Cycle I, the average student activity score was 1.95, categorized as fair, while in Cycle II it increased to 3.15, categorized as good. In addition, students’ learning outcomes also improved in each cycle. The use of concrete media in the form of sticks and the Math Adventure game helped students understand the concept of multiplication in a more concrete and contextual way. Therefore, the Problem Based Learning (PBL) model proved to be effective in improving students’ cognitive abilities in learning multiplication in elementary school mathematics.